An empirical investigation into the characteristics of local manufacturing enterprises using management consultancy services. - Quek, Thian Seong. (2009)
As the Singapore economy evolves from a developing phase to a more mature phase, and given the backdrop of an increasingly uncertain world economy, the need to nurture a competitive local private sector to provide future economic growth becomes increasingly important. From an organization's point of view, its ability to adapt to changes would significantly affect its competitiveness. Engaging the services of management consultants is one way of assisting local enterprises to manage and implement the necessary changes needed. However, evidence suggests that not many local enterprises are doing so. In order to understand why local enterprises are not using consultancy services and to encourage wider usage of consultancy services, it seems reasonable to examine the characteristics of both the users and non-users of such services. This forms the main research issue in this study.